Synthesis and Characterization of Azo Schiff Bases and their β-Lactam Derivatives - Shinde, Anil H.; Patil, C.J. (Asian Journal of Chemistry, 2020)
Azo salicylaldehyde (I5) was synthesized by reaction of 5-bromo-salicylaldehyde with diazonium salt of 4-nitroaniline by diazotization method. Thus, synthesized azoaldehyde was treated with variable 2-aminobenzothiazoles (I6a-f) to synthesize the Schiff bases (I7a-f). The β-lactam derivatives (I8a-f) were also synthesized. All the newly synthesized compounds were characterized by TLC, UV-visible and FT-IR techniques.